ANALISIS STRUKTUR BATIN PUISI 3 MERAWAT KATA KARYA GERARDUS WERUIN, NANO L. BASUKI, DAN PAY JAROT SUJARWO - Hermawan, Teguh (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study attempts to give a description about the inner structure of poetry association of anthology poetry 3 Merawat Kata by Gerardus Weruin, Nano L Basuki, and Pay Jarot Sujarwo. The method used is desriptive method  with qualitative approach. Data sources for this research are words of the poetries from anthology 3 Merawat Kata by Gerardus Weruin, Nano L Basuki, and Pay Jarot Sujarwo. Datas collected used data cards. Techniques used is a study documentation.  Analysis of the data shows that the theme of poetry that dominant  is described a human being in undergo the process of life , as was the theme of grief , failure , loyalty and romance. Bring  up the theme human relations and the environment.The feeling that appeared divided into three, namely feeling melankolic, sad, sorry, confused, pity, upset, the optimistic feeling, and feeling disappointed. Tone which appeared in the peotries is a solemn , melankolik , criticism and protested. There are three message which appeared in this anthology, which is asked human to always be gracefull, understanding humanlife value, and never wasting time for nothing. This anthology also asked people to keep the unity, loyalty and save the environment. In addition , this poem also decree that the reader excited in maintaining nature , keep meeting and eager to study. Keywords : anthology. Poem. Inner structure. Tone. Theme. Feeling. Message.